Long‐term outcomes of endoscopic papillary balloon dilation and endoscopic sphincterotomy for bile duct stones. Issue 3 (8th November 2012) - Natsui, Masaaki; Saito, Yu; Abe, Satoshi; Iwanaga, Akito; Ikarashi, Satoshi; Nozawa, Yujiro; Nakadaira, Hiroto
<x xml:space="preserve">Abstract</x> Aim We recently reported that endoscopic papillary balloon dilation (EPBD) might suppress biliary bacterial contamination better than endoscopic sphincterotomy (EST) in patients with small bile duct stones (diameter ≤8 mm). In the present study, we evaluated immediate and long‐term outcomes of endoscopic papillary balloon dilation with regard to stone size. Methods We allocated 474 patients alternately to the two procedures. The patients were classified according to stone diameter (≤8 mm or >8 mm) and outcomes (i.e. complete stone removal, early complications, and late complications) were compared. The predictive risk factors for late complications were also investigated. Results In patients with small stones, complete stone removal rate and early complication rate were similar between the two procedures; the incidence of pancreatitis was higher after EPBD, although the difference was not significant. Late complication rate and stone recurrence rate were significantly lower after EPBD than after EST (5.3% vs 17.3%, P = 0.009; 4.4% vs 12.7%; P = 0.048, respectively). In patients with large stones who underwent EPBD complete stone removal rate and late complication rate were lower, but the incidence of pancreatitis was higher. However, these differences were not statistically significant. Multivariate analysis showed that the increased risk of bactobilia following EPBD for large stones or EST, and the gallbladder with stones in situ were independent risk factors for late complications. Conclusions EPBD produced significantly better long‐term outcomes than EST in patients with small bile duct stones.